Seasonal Differences in Structural and Genetic Control of Digestibility in Perennial Ryegrass - Colas, Vincent; Barre, Philippe; van Parijs, Frederik; Wolters, Lukas; Quitté, Yannick; Ruttink, Tom; Roldán-Ruiz, Isabel; Escobar Gutiérrez, Abraham J.; Muylle, Hilde (Frontiers in Plant Science, 2022)
Perennial ryegrass is an important forage crop in dairy farming, either for grazing or haying purposes. To further optimize the forage use, this study focused on understanding forage digestibility in the two most important cuts of perennial ryegrass, the spring cut at heading and the autumn cut. In a highly diverse collection of 592 Lolium perenne genotypes the organic matter digestibility (OMD) and underlying traits such as cell wall digestibility (NDFD) and cell wall components (cellulose, hemicellulose and lignin) were investigated during 2 years. A high genotype x season interaction was found for OMD and NDFD, indicating differences in genetic control of these forage quality traits in spring versus autumn. OMD could be explained by both the quantity of cell wall content (NDF) and the quality of the cell wall content (NDFD). The variability in NDFD in spring was mainly explained by differences in hemicellulose. A 1% increase of the hemicellulose content in the cell wall (HC.NDF) resulted in an increase of 0.81% of NDFD. In autumn, it was mainly explained by the lignin content in the cell wall (ADL.NDF). A 0.1% decrease of ADL.NDF resulted in an increase of 0.41% of NDFD. The seasonal traits were highly heritable and showed a higher variation in autumn versus spring, indicating the potential to select for forage quality in the autumn cut. In a candidate gene association mapping approach, in which 503 genes involved in cell wall biogenesis, plant architecture and phytohormone biosynthesis and signaling, identified significant QTLs which could explain from 29% to 52% of the phenotypic variance in the forage quality traits OMD and NDFD, with small effects of each marker taken individually (ranging from 1 to 7%). No identical QTLs were identified between seasons, but within season, some QTLs were in common between digestibility traits and cell wall composition traits confirming the importance of hemicellulose concentration for spring digestibility and lignin concentration in NDF for autumn digestibility.